Evaluation of the vestibular/ocular motor screening assessment in active combat sport athletes: an exploratory study. (3rd July 2022) - Brown, Daniel A; Grant, Gary; Evans, Kerrie; Leung, Felix T.; Hides, Julie A.
ABSTRACT: Objective: The first aim of this study was to compare the results of the vestibular/ocular motor screening (VOMS) in combat sport athletes with a healthy control population. Second, to explore differences between athletes with and without a concussion history. Third, to examine the relationship between VOMS and the Post-Concussion Symptom Scale (PCSS) in combat sport athletes. Participants: Forty active male combat sport athletes and 40 healthy male control participants were recruited from 4 clubs and a University in Australia. Methods: Participants completed the VOMS in a primary care physiotherapy clinic. Participants completed an injury questionnaire and the PCSS. Results: An "abnormal" score in at least one subtest or near point convergence (NPC) was recorded in 45% of the combat group compared with 22.5% of the control group. All VOMS scores and NPC distance were greater in the combat group compared with control group ( p < 0.05). The VOMS scores were found to be moderately positively correlated with the PCSS. There was no difference in VOMS between athletes with and without a history of concussion ( p > 0.05). Conclusion: VOMS scores differed between combat sport athletes and control participants. The PCSS may aid clinicians in identifying athletes who have underlying vestibular/oculomotor impairment.